(untitled) - Franzosi, Roberto (Cambridge, UK, 2004)
This book illustrates a set of tools - story grammars, relational data models, and network models - that can be profitably used for the collection, organization, and analysis of narrative data in socio-historical research. A story grammar, or Subject-Action-Object and their modifiers, is the linguistic tool the author uses to structure narrative for the purpose of collecting event data. Relational database models make such complex data collection schemes practically feasible in a computer environment. Finally, network models are a statistical tool best suited to analyze this type of data.
Keywords: Social sciences,Content analysis (Communication),Khoa học xã hội,Phân tích diễn ngôn, Tường thuật,Phân tích nội dung (Sự truyền đạt),Discourse analysis, Narrative; Research,Nghiên cứu